Early blastulation (EB) of day 4 embryo is predictive of outcomes in single embryo transfer (SET) cycles - Cheng-En Hsieh; Robert Kuo-Kuang Lee; Fang-Ju Sun; Ryh-Sheng Li; Shyr-Yeu Lin; Ming-Huei Lin; Yuh-Ming Hwu (Elsevier, 2018)
Objective: The aim of this study was to assess whether the early blastulation (EB) of day 4 embryo is a useful predictor for outcomes in fresh elective single embryo transfer (eSET) cycles. Materials and methods: We retrospectively enrolled patients undergoing fresh SET cycles in our hospital from April 2014 to September 2016 and met with the following criteria: 1) age <38 years, 2) first IVF/ICSI cycle, 3) at least two blastocysts with morphological grading better than or equal to 4BB. Results: A total of 81 patients were included. Of whom, 55 patients (68%) had undergone eSET with embryos that had early blastulation on day 4 while the other 26 patients had had no EB. Early blastulation has shown a higher rate of good blastocyst (84.3% vs. 60.5%, p < 0.0001). The clinical pregnancy rate of EB group was significantly higher than that of non-EB group (56.4% vs. 27.0%, p = 0.013). There is also a tendency in EB group to have a lower abortion rate (3.23% vs. 28.6%, p = 0.081). Conclusions: EB on day 4 is a useful predictor of the quality of the following embryos (i.e. day 5 embryo). It is a simple tool in selecting the best embryo to get a higher pregnancy rate in fresh eSET cycles.Trial registration: This study was supplementally registered by the MacKay Memorial Hospital Institutional Review Board on April 18, 2017 (registration No. 17MMHIS039e). Keywords: Early blastulation, Single-embryo transfer, Blastocyst morphology, Clinical pregnancy